KITS: a national system for document supply in Turkey - Çimen, Ertuğrul; Çelikbaş, Sema; Çelikbaş, Zeki; Tuğlu, Ayhan; Manyas, Mehmet (Emerald Group Publishing Limited, 2009)
Purpose – The paper aims to describe a new national system for resource sharing and document supply in Turkey. Design/methodology/approach – The paper takes a historical and descriptive approach. Findings – KITS has been very successful in linking academic and other institutions in Turkey to an effective and efficient system of document supply. This is illustrated by figures provided on its expansion in the last two years. Practical implications – The paper is useful for all librarians concerned with national document supply systems, especially in the developing world. Originality/value – This is the first published review of the national system that is transforming document supply in Turkey, and it deals frankly with the obstacles that KITS faces, at the same time indicating the ways in which success has been achieved.
This article is a revised and updated version of a presentation given at the Document Delivery and Resource Sharing Section at the IFLA Conference in Milan, 23-27 August 2009. It is published with the kind cooperation of IFLA.
Keywords: Document supply; Interlending; Turkey